2010
DOI: 10.1002/cbdv.200800342
|View full text |Cite
|
Sign up to set email alerts
|

Casearin X, Its Degradation Product and Other Clerodane Diterpenes from Leaves of Casearia sylvestris: Evaluation of Cytotoxicity against Normal and Tumor Human Cells

Abstract: An EtOH extract of the leaves of Casearia sylvestris afforded new clerodane diterpene, casearin X, together with the known compounds casearins B, D, L, and O, and caseargrewiin F. Casearin X degraded to the corresponding dialdehyde when stored in CDCl(3). The diterpenes isolated were cytotoxic to human cancer cell lines, with caseargrewiin F being the most active and the new clerodane, casearin X, the second active compound with IC(50) values comparable to the positive control doxorubicin. All isolated diterpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…One of these studies on hydroethanolic extract of C. sylvestris leaves showed no toxicity after a single (acute) or repeated exposure (28 and 90 days) and indicated that the LD50 (lethal dose for 50% of the population) of this extract was greater than 2000 mg/kg. Other previous studies have also reported low in vivo and in vitro toxicity of C. sylvestris (Basile et al, 1990;Ferreira et al, 2014;Maistro et al, 2004;Santos et al, 2010). However, no study has investigated the effects of this species during critical periods of development, particularly the organogenesis period, which is when the main organs develop.…”
Section: Introductionmentioning
confidence: 96%
“…One of these studies on hydroethanolic extract of C. sylvestris leaves showed no toxicity after a single (acute) or repeated exposure (28 and 90 days) and indicated that the LD50 (lethal dose for 50% of the population) of this extract was greater than 2000 mg/kg. Other previous studies have also reported low in vivo and in vitro toxicity of C. sylvestris (Basile et al, 1990;Ferreira et al, 2014;Maistro et al, 2004;Santos et al, 2010). However, no study has investigated the effects of this species during critical periods of development, particularly the organogenesis period, which is when the main organs develop.…”
Section: Introductionmentioning
confidence: 96%
“…The genus Casearia includes 180 species [3] and belongs to Salicaceae family. This family is constituted of 54 genera and 1,200 species, composed of trees or bushes of cosmopolitan distribution [4], and considered as source of clerodane-type diterpenes [5][6][7]. In the Yucatan peninsula there are four species of the genus Casearia [8], including Casearia corymbosa Kunth.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the cytotoxicity against human tumor cell lines [2,3,5,[11][12][13][14][15][16], casearin X and a pool of casearins inhibited tumor growth in mice when orally administered [5]. Casearins promoted cell death via apoptotic pathways in vitro [16] and were selective to tumor cell lines [15]. C. sylvestris leaf extracts and casearin-type diterpenes showed antiulcer activity after oral administration in rats [10,17].…”
mentioning
confidence: 99%
“…However, the oral absorption and metabolism processes of the clerodane diterpenes cas B and casg F were never explored. In vitro assays simulating oral administration of casearins J and O generated the respective dialdehydes as main degradation products and metabolites [18], as previously described for casearin X [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation